Anti-Money Laundering Regulations in the Crypto-Based Fintech Sector of Indonesia and Malaysia: Lessons from the European Union - Triana Dewi Seroja; Elysia Monica Anggelina; Tantimin Tantimin (Vifada Assumption Journal of Law, 2026)
Purpose: This study aims to analyze and compare anti-money laundering (AML) regulations in the crypto-based fintech sectors of Indonesia and Malaysia, using the European Union (EU) as a benchmark for best practices. The EU is chosen as a benchmark primarily due to potential concrete lessons from the MiCA framework and AML Directives. This benchmark also serves as the main element of novelty, as it combines comparative analysis of Indonesia and Malaysia with the assessment of the EU’s regulatory advantages under its harmonized crypto-asset regulatory model. Research Design and Methodology: The research employs a normative doctrinal legal method with statutory, comparative, and conceptual approaches, relying on qualitative analysis of secondary legal materials. Findings and Discussion: The findings reveal that although Indonesia and Malaysia have established AML frameworks, both face significant challenges in regulatory effectiveness, particularly due to fragmented supervision, limited coordination, and gaps between regulation and implementation. In contrast, the European Union demonstrates a more comprehensive and harmonized regulatory model through instruments such as MiCA and AML Directives, which enhance transparency, cross-border cooperation, and regulatory adaptability. Implications: These findings imply that Indonesia and Malaysia need to adopt and contextualize EU best practices by strengthening institutional integration, improving regulatory coherence, and enhancing compliance mechanisms to ensure a more effective and resilient AML regime in the evolving digital financial landscape.